Biosurfactant activity of phylloplane bacteria from an ornamental plant, Colocasia esculenta L. (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Bukhori A, Suryanto D, Nurtjahja K. 2022. Biosurfactant activity of phylloplane bacteria from an ornamental plant, Colocasia esculenta L. Biodiversitas 23: 3108-3114. Biosurfactants are surface-active molecules produced by living organisms predominantly by microorganisms with amphiphilic properties. Exploration of biosurfactant-producing bacteria has been promoted to find the suitable agent for mass production in the laboratory following its biochemical and genetic modification. Leaf-colonizing bacteria or phyllosphere bacteria are of great interest, including those colonizing the surface of ornamental plants which are still understudied. This study aimed to isolate the biosurfactant-producing bacteria from an ornamental plant, Colocasia esculenta L and to determine their physical characteristics. Four bacterial isolates coded as IC1, IC3, IC4 and IC5 were recovered from the surface of C. esculenta and were tested positive for their growth under Bushnell-Haas agar + 1% olive oil (v/v) as the sole carbon source. Two isolates, namely IC3 and IC5, later molecularly identified as Bacillus cereus and Alcaligenes faecalis produced the highest biosurfactant concentration (IC3 = 157 ppm, IC5 = 106 ppm) on 10th day incubation based on a colorimetric test using rhamnolipid as a standard solution. Crude biosurfactants produced by A. faecalis IC5 showed better physical attributes than B. cereus IC3 in terms of surface tension, emulsification index, and oil spreading capability on four different hydrophobic compounds i.e., kerosene, solar fuel, octane fuel (Pertalite, Pertamax). The results of this study confirmed the existence of biosurfactant-producing bacteria in C. esculenta and the possibility of developing prominent strains for the treatment of hydrocarbon pollution in the environment.
Keywords: Alcaligenes, Bacillus, biosurfactant, Colocasia esculenta, phyllosphere bacteria